Examining academic confidence and study support needs for university students with dyslexia and/or developmental coordination disorder. (24th October 2020) - Sumner, Emma; Crane, Laura; Hill, Elisabeth L.
Abstract : Higher education providers are seeing a shift from externally funded support for students with specific learning difficulties (SpLD), to a need to develop more inclusive practices generally. However, the precise needs of students with different SpLD diagnoses is unknown. A total of 367 students in England and Wales (163 students with dyslexia, 50 students with developmental coordination disorder [DCD/"dyspraxia"], 62 students with dyslexia and DCD, and 92 non‐SpLD students) completed an online questionnaire to determine: (a) how confident they are with their study‐related capabilities, (b) the types of support they access, and (c) their views on current inclusive practices. Students with dyslexia and students with dyslexia/DCD reported lower confidence in their grades and studying than non‐SpLD students, and accessed more technology‐related support than students with DCD only. Examination accommodations supporting writing were common for all SpLD students. Inclusive practices were perceived positively, although different priorities were seen across groups. The findings demonstrate the complexities inherent in providing effective support for all students at university, with the varied profiles across and within SpLD groups suggesting that an individualized approach is necessary. Practical implications are discussed.